Short Communication -Orodental Perspective of Substance Abusers - S.Angelinteena (Institute of Medico-legal Publications Pvt Ltd, 2020)
Substance Abuse is the habitual taking of illegal drugs by an individual or a group of people. Mostcommonly used these kind of drugs are Marijuana, Cocaine, Amphetamines, Heroin, Hallucinogens etc….The oral cavity reflects, the deleterious effects of these drugs. This short communication attempt to highlightthe various clinical manifestations of these drugs seen in oral cavity.